Management Competencies and Trust in a Private Service Company - Cortez Giraldo, Luis Martín (2021)
This non-experimental, descriptive and correlational research aims at identifying the relationship between the management competencies of middle managers and trust within the work teams of a private services company. The sample consisted of the total population of the company. The management competencies scale of García-Lombardía, Cardona and Chinchilla and the trust dimension of the Lencioni team assessment scale were used; both with adequate psychometric properties for the study. The results show with a 99% probability that trust is significantly and positively related to management competencies, i.e., the greater development of management competencies, the greater the trust within the work teams; similarly, if management competencies are less developed, the lower the level of trust.